FASHION AND CONSUMER CULTURE OF NORTH KOREAN WOMEN AND THE ‘CULTURAL TURN’ TOWARD HARMONY - Do, Jein; Park, Mincheol (Journal of Dharma, 2021)
This paper seeks to set a new direction for a ‘Cultural Turn’ toward harmony in re-examining the Korean Cold War to promote a sustainable inter-Korean scholarly dialogue and enhance mutual understanding. Based on the ‘Cultural Turn’ in Cold War studies, the concept of ‘commonality’ in ‘Humanities for Unification’ (t’ongil inmunhak), parallels drawn with the decline of socialist fashion in Eastern Europe, and discussions on the achievement of UN Sustainable Development Goals (SDGs) such as Gender Equality and Women Empowerment (SDG 5) in the unique context of North Korea where ‘gender equality’ and ‘namjonnyŏbi (superior men, inferior women)’ coexist, the present analysis looks into the clothing and consumer culture of women in the 1980s to explore the nuances and complexities specific to the materiality of chuch’e (self-reliance) socialism and gauge the feasibility of SDG 5 in the North Korean context by focusing on the agency of women in their own self-empowerment rather than the patriarchal socialist state or institutions. The interviews with North Korean defectors demonstrate the evolving state-society negotiations concerning standard and new styles, domestic and transnational means of consumption, and regulation and deregulation for the revitalization of socialism. By exposing the normalizing qualities of chuch’e socialism and the active role of women in their formation, the ‘Cultural Turn’ explores North Korea’s distinct experience of modernity to pave the way for viable inter-Korean academic exchange between the worlds of han’gukhak and chosŏnhak.